Providers’ Perspectives on Implementing a Multiple Family Group for Children with Disruptive Behavior - Hamovitch, Emily K. (J Child Fam Stud, 2019)
OBJECTIVES: The adoption of research-supported treatments is contingent upon multiple interactional levels, including provider level factors. Provider-level factors have been shown to be critical to uptake. The purpose of this study is to examine the relationship between sociodemographic factors, attitudes, and perceived barriers/facilitators to implementation through a comparative approach involving practitioners trained to facilitate a multiple family group intervention for children with disruptive behavior. METHODS: Participants included 91 practitioners who participated in an intervention study regarding barriers to adopting an evidence-based practice. Demographic characteristics were collected via a socio-demographic questionnaire. Barriers and facilitators were assessed via open-ended questions as well as a scale, developed by the authors and guided by the Consolidated Framework for Implementation Research that explored provider views regarding the intervention, the systemic and organizational context, experience facilitating groups and involving families in treatment, and feelings toward involving families in treatment. Between group analyses were conducted to examine demographic and characteristic differences of providers by implementation status. Independent samples t-tests for continuous characteristics and chi-square tests for categorical characteristics were used. Responses to open-ended questions were compiled, reviewed, and coded, and frequencies and percentages were calculated. RESULTS: Results demonstrated that providers who implemented the intervention were significantly more likely to have favorable attitudes toward the intervention compared to those who did not implement it. Prior experience facilitating groups was significantly associated with implementation. Common barriers to implementation included ineligible caseloads and feeling unqualified to deliver the intervention. CONCLUSIONS: Further attention on improving recruitment rates and promoting adequate training and supervision is needed.